2013
DOI: 10.1186/1472-6963-13-222
|View full text |Cite
|
Sign up to set email alerts
|

Distance and utilisation of out-of-hours services in a Norwegian urban/rural district: an ecological study

Abstract: BackgroundLong travel distances limit the utilisation of health services. We wanted to examine the relationship between the utilisation of a Norwegian out-of-hours service and the distance from the municipality population centroid to the associated casualty clinic.MethodsAll first contacts from ten municipalities in Arendal out-of-hours district were registered from 2007 through 2011. The main outcomes were contact and consultation rates for each municipality for each year. The associations between main outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 8 publications
7
47
4
1
Order By: Relevance
“…Especially outside office hours, when municipal health care centers are closed, people may prefer to call for an EMS unit rather than make their way to a distant emergency department. Similar findings were found in a Norwegian study in which increased distance was associated with lower rates of all contact types to casualty clinics except telephone consultations by a doctor . This correlation between NTR outside office hours and the distance to the emergency department was an interesting finding which may be difficult to interpret.…”
Section: Discussionsupporting
confidence: 82%
“…Especially outside office hours, when municipal health care centers are closed, people may prefer to call for an EMS unit rather than make their way to a distant emergency department. Similar findings were found in a Norwegian study in which increased distance was associated with lower rates of all contact types to casualty clinics except telephone consultations by a doctor . This correlation between NTR outside office hours and the distance to the emergency department was an interesting finding which may be difficult to interpret.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, people who live a short distance from an emergency clinic and those with low socio-economic status tend to use emergency health care services more often [19–22]. A study conducted in Bergen, Norway, found that three of four patients had not tried to contact their RGP before attending an emergency primary health care clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Rural patients often delay seeking help until their PCP is available in-hours, when they are not on call (Campbell et al, 2006). In a similar vein, increasing travel distance is associated with lower use of OOH services, even for the most acute cases (Raknes et al, 2013). Together the body of evidence suggests that in rural and remote areas, access to OOH primary care is more challenging because of more limited medical infrastructure and workforce shortages, which overall increases travelling distance for sparsely distributed populations.…”
mentioning
confidence: 99%